Implementasi Green Banking dalam Mendukung Transisi Ekonomi Hijau di Indonesia Studi Bank Syariah Indonesia Kantor Cabang Adam Malik Kota Bengkulu - Meidhe Ade Maharani; Idwal B; Katra Pramadeka (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2026)
This study aims to analyze the implementation of green banking in supporting Indonesia’s transition toward a green economy through a case study at Bank Syariah Indonesia (BSI) Bengkulu Adam Malik Branch. The research is motivated by climate change urgency and Indonesia’s Nationally Determined Contribution (NDC) commitment to reduce greenhouse gas emissions by 29% by 2030. Using a qualitative case study approach, data were collected through interviews and documentation. The analysis employs Edward III’s policy implementation theory and maqāṣid al-sharī‘ah framework. Findings indicate that green banking has not yet been formulated as a specific product but has been integrated through digital banking services, the BYOND by BSI application, e-Emas features, and paperless systems. The implementation aligns with Islamic objectives of protecting wealth and life while supporting sustainable finance.